Changing Indications for Cervical Cerclage Following the Introduction of Routine Ultrasound Surveillance of Cervical Length for Prediction and Prevention of Preterm Birth - Rawashdeh H; Ramachandran A; Yang JM; Blain G; Hyett J (Dove Medical Press, 2024)
Hasan Rawashdeh,1,2 Aparna Ramachandran,1 Jenny M Yang,1 Gemma Blain,1 Jon Hyett1,3 1Department of Women and Babies, Royal Prince Alfred Hospital, Camperdown, NSW, Australia; 2Department of Obstetrics and Gynaecology, Jordan University of Science and Technology, Irbid, Jordan; 3Department of Obstetrics and Gynaecology, Western Sydney University, Sydney, NSW, AustraliaCorrespondence: Hasan Rawashdeh, Department of Obstetrics and Gynaecology, Jordan University of Science and Technology, Irbid, Jordan, Tel +00 962 7 9828 4038, Email hmrawashdeh@just.edu.joBackground: Preterm birth (PTB) is associated with significant neonatal mortality and morbidity. Universal measurement of cervical length has been proposed as a screening tool to direct intervention to prevent PTB.Aim: To assess the impact of the introduction of sonographic mid-trimester cervical length screening on the use of cervical cerclage and PTB.Material and Methods: A retrospective cohort study reviewed two groups of women who underwent cervical cerclage before and after the introduction of universal sonographic cervical length screening. Demographics and outcomes were compared using Student's t test, Fisher's Exact test and Kaplan-Meier analysis.Results: Following introduction of universal cervical length screening, the overall rate of cerclage increased from 2.5/1000 births to 6.0/1000 births (p < 0.01). There was a reduction in the proportion of sutures placed purely based on maternal history (50.0% to 30.4%; p < 0.001), while the proportion of sutures placed following ultrasound assessment increased in both high- (21.7 to 36.6%) and low-risk (11.7% to 30.4%) women (p < 0.001). The overall rate of PTB < 37 weeks in women has a cerclage was 25.7% and was highest in women undergoing rescue cerclage (64.3%; p < 0.01). There was no difference in the rate of PTB between high- and low-risk women undergoing history- or ultrasound-indicated cerclage. Mean pregnancy length was most prolonged in low-risk women undergoing ultrasound-indicated cerclage, extending gestation from 33.9 to 38.3 weeks (p < 0.01).Conclusion: Universal cervical length screening results in an increase in the use of cerclage, specifically on the basis of the ultrasound findings. Women who were at low risk but then underwent ultrasound-indicated cerclage experienced most prolongation of pregnancy. Women who were at high risk but had a suture on the basis of ultrasound findings-indicated cerclage represent an alternative method of management with no significant difference in the gestational age of delivery.Keywords: cerclage, premature birth, cervical length measurement, progesterone, ultrasonography